EFEKTIVITAS VIDEO ANIMASI TERHADAP HASIL BELAJAR SISWA - Cornellia Christin Adiati; Rangga Firdaus; Muhammad Nurwahidin (Akademika : Jurnal Teknologi Pendidikan, 2023)
The learning process involves teachers working with students and other learning tools in the classroom. In this era of globalization, science and technology are increasingly advanced which demands regeneration of society as a whole, especially in the education sector. In an effort to improve the quality of education, especially in the learning process, the growing development of science and technology places demands on the education sector to always adapt to technological changes. The learning process can be greatly helped by video-based media, both for learning activities. The research carried out has the aim of being able to find out the use of video media with the aim of the effectiveness of powtoon media in increasing students' cognitive development in natural science material. SLR (Systematic Literature Review) is the chosen research methodology for this study. All education related items according to Google Schoolar and SINTA are cataloged and reviewed to collect data. According to 10 research findings, animated videos have an average feasibility of 89.3% when used in the science learning process because they have a positive impact on student learning outcomes.